SH.SEYITOVTIŃ «XALQABAD» ROMANINIŃ LEKSIKALIQ O‘ZGESHELIKLERI - Erjanova, D.Q. (SCIENCE and SOCIETY, 2023)
In the article the lexical features of the novel “Khalkabad” of the great Karakalpak poet Sh.Seitov, poet’s skills of using synonyms, antonyms, homonyms, phraseologisms is learnt.